2013
DOI: 10.1021/jm301355j
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective Inhibition of Histone Deacetylase 6 (HDAC6) Does Not Require a Surface-Binding Motif

Abstract: Hydroxamic acids were designed, synthesized, and evaluated for their ability to selectively inhibit human histone deacetylase 6 (HDAC6). Several inhibitors, including compound 14 (BRD9757), exhibited excellent potency and selectivity despite the absence of a surface-binding motif. The binding of these highly efficient ligands for HDAC6 is rationalized via structure-activity relationships. These results demonstrate that high selectivity and potent inhibition of HDAC6 can be achieved through careful choice of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
119
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 46 publications
5
119
1
Order By: Relevance
“…Compound 5.32 is a potent inhibitor of Plasmodium falciparum (50% growth inhibition at ≈20 nM), with a comparable antimalarial activity with potent broad spectrum HDAC inhibitors, although its toxicity profile is more acceptable [109]. Recently reported hydroxamates include the unsaturated linker-, sulfonamide capcontaining C1A (5.33), endowed with good in vivo PK and efficacy against colon tumors [141]; the unsaturated linker-, furylamine cap-containing 5.34, showing good solubility [142]; the arylalkene linker-containing, phenyl-capped dual HDAC6-HDAC8 inhibitor 5.35, capable of cellular a-tubulin acetylation without any effect on histone deacetylation [143]; the phenylmethyl linker-containing, dihydroquinoxalinone-capped chiral compound 5.36, which shows moderate selectivity for HDAC6 and cellular activity (a-tubulin acetylation) [144]; and the linker-less pyrroline compound 5.37 ( Figure 5.7), which achieves good HDAC6 selectivity within an extremely small structure [145]. Homology models of HDAC1 and HDAC6 are used to identify a more drug-like, HDAC6-selective hydroxamate inhibitor [146].…”
Section: Hdac6mentioning
confidence: 99%
“…Compound 5.32 is a potent inhibitor of Plasmodium falciparum (50% growth inhibition at ≈20 nM), with a comparable antimalarial activity with potent broad spectrum HDAC inhibitors, although its toxicity profile is more acceptable [109]. Recently reported hydroxamates include the unsaturated linker-, sulfonamide capcontaining C1A (5.33), endowed with good in vivo PK and efficacy against colon tumors [141]; the unsaturated linker-, furylamine cap-containing 5.34, showing good solubility [142]; the arylalkene linker-containing, phenyl-capped dual HDAC6-HDAC8 inhibitor 5.35, capable of cellular a-tubulin acetylation without any effect on histone deacetylation [143]; the phenylmethyl linker-containing, dihydroquinoxalinone-capped chiral compound 5.36, which shows moderate selectivity for HDAC6 and cellular activity (a-tubulin acetylation) [144]; and the linker-less pyrroline compound 5.37 ( Figure 5.7), which achieves good HDAC6 selectivity within an extremely small structure [145]. Homology models of HDAC1 and HDAC6 are used to identify a more drug-like, HDAC6-selective hydroxamate inhibitor [146].…”
Section: Hdac6mentioning
confidence: 99%
“…An alternatively-capped, phenyllinked HDAC6-selective inhibitor, tubastatin A (15 nM, >57-fold vs all HDACs), was described by Butler et al in 2010 [60], and subsequent analogs with improved potency and selectivity were later reported [61]. In an effort to identify novel, selective, and highly efficient HDAC6 inhibitors, Wagner et al [62] reported a linker-based strategy exploiting close contacts and structural differences between the various isoforms within the catalytic binding domain of HDAC6. BRD9757, cyclopentenyl hydroxamic acid, represents the most ligand-efficient HDAC6 selective inhibitor reported to date (ligE=0.83) and demonstrates that linker elements alone can play a significant role in imparting isoform selectivity.…”
Section: Hydroxamic Acidsmentioning
confidence: 99%
“…2). HDAC inhibitors were proven to fight against cancer and other human afflictions including psychiatric, metabolic and infectious diseases (Librizzi et al 2012;Wagner et al 2013) (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%